2020
DOI: 10.1111/1750-3841.14986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soybean isoflavone on metabolism of rat osteoblasts and cytokines in vitro

Abstract: The effects and mechanisms of soybean isoflavone on osteoblast (OB) proliferation in vitro were investigated. Fifty female Wistar rats were randomly divided into five groups with 10 rats in each group. Rat OBs were separated and cultured. The first generation of OBs cultured for 48 hr at various concentrations of isoflavone were set as the experimental groups, the OBs exposed to estradiol (E 2 ) culture were considered as positive control group. The biological characterization of OBs was investigated by phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Unfermented soybean products mainly exist in the form of glycosides, and fermented soybean products mainly exist in the form of aglycone, which has higher bioavailability, as reflected in this experiment (Figure 10). Soybean isoflavones are good antioxidants and tumor suppressors, especially for hormone-related tumors, such as breast cancer and prostate cancer; they can reduce blood cholesterol levels, coronary atherosclerosis, and peripheral arterial vascular damage, and their weak estrogen-like effect has a certain preventive effect on menopausal syndrome and bone loss in women (52,53). In addition, soybean isoflavones can improve lipid metabolism, and they can enhance nonspecific immunity and anti-inflammatory effects, mainly related to daidzein and genistein (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Unfermented soybean products mainly exist in the form of glycosides, and fermented soybean products mainly exist in the form of aglycone, which has higher bioavailability, as reflected in this experiment (Figure 10). Soybean isoflavones are good antioxidants and tumor suppressors, especially for hormone-related tumors, such as breast cancer and prostate cancer; they can reduce blood cholesterol levels, coronary atherosclerosis, and peripheral arterial vascular damage, and their weak estrogen-like effect has a certain preventive effect on menopausal syndrome and bone loss in women (52,53). In addition, soybean isoflavones can improve lipid metabolism, and they can enhance nonspecific immunity and anti-inflammatory effects, mainly related to daidzein and genistein (54,55).…”
Section: Discussionmentioning
confidence: 99%
“…Soybean isoflavone (SI) is a bioactive secondary metabolite formed during soybean growth. Studies have shown that SI can protect the cardiovascular system through its antioxidant effects [ 195 197 ]. SI enhanced the activity of SOD, decreased the level of thiobarbituric acid reactant in plasma, and enhanced the antioxidant capacity of plasma, as well as the activity of GSH-PX in erythrocytes [ 198 ].…”
Section: Application Of Antioxidant Natural Drugs For Cardiovasculmentioning
confidence: 99%
“…It has a molecular structure comparable to estrogen and exists in nature as a molecule with a polyphenolic hydroxyl group called β-glucoside and can be induced by estrogen. Owing to the antiestrogenic and estrogenic activities, it is often referred to as a selective estrogen receptor modulator [ 50 , 51 ]. These compounds may be protective against osteoporosis due to their ability to exert osteogenic and antiresorptive actions on bone, particularly on bone turnover and growth [ 52 , 53 ].…”
Section: Types Of Flavonoidsmentioning
confidence: 99%